Molecular characterization of ten viral pathogens causing calf diarrhea in Hanwoo (Bos Taurus coreanae) by next generation sequencing - Jeong-Byoung Chae; Won Gyeong Kim; Shinae Song; Joon-Seok Chae (BMC Veterinary Research)
Abstract Background Calf diarrhea remains a significant concern in the global cattle industry, leading to considerable economic losses. Infectious pathogens are among the primary causes of this disease. In this study, the prevalence of 7 pathogens—bovine rotavirus (BRV), bovine coronavirus (BCV), bovine viral diarrhea virus (BVDV) types 1 and 2, Cryptosporidium parvum, Giardia spp., and Eimeria spp.—associated with calf diarrhea was investigated using polymerase chain reaction (PCR). A metagenomic approach was also applied to identify additional RNA viral pathogens from unknown causes of diarrheic fecal samples in the Republic of Korea (ROK). Results A total of 810 fecal samples from Hanwoo calves (Bos taurus coreanae) were collected, consisting of 526 normal samples (267 with a fecal score of 0 and 259 with a fecal score of 1) and 284 diarrheic samples (178 with a fecal score of 2 and 106 with a fecal score of 3). All 7 pathogens were detected by PCR in feces and their detection rates and mean fecal scores for each were as follows: BRV (14.0%, 1.41), BCV (3.2%, 1.42), BVDV1 (2.1%, 1.35), BVDV2 (4.9%, 1.33), C. parvum (9.8%, 1.66), Eimeria spp. (1.9%, 1.73), and Giardia spp. (0.9%, 0.71). Among these pathogens, BRV (p = 0.004), C. parvum (p < 0.001), and Eimeria spp. (p = 0.027) showed an increase in prevalence with higher fecal scores. Twenty-one fecal samples negative for all pathogens were randomly selected and subjected to high-throughput sequencing to identify RNA viral pathogens associated with calf diarrhea. This approach led to the identification of nearly complete genomic sequences for bovine astrovirus, bovine enterovirus, bovine kobuvirus, bovine nebovirus, bovine norovirus, bovine boosepivirus B, bovine parechovirus, bovine torovirus, C. parvum virus 1, and hunnivirus. Conclusions This study represents the first investigation of hunnivirus presence and provides a comprehensive description of the nearly complete genomes of 10 viruses associated with calf diarrhea in the ROK. The findings contribute to a better understanding of the epidemiology and molecular characteristics of calf diarrhea-associated pathogens in the ROK, highlighting the potential application of high-throughput sequencing for diagnosing other diseases.